STYLES IN FASHION ILLUSTRATION DESIGN: IMAGE, AESTHETICS - Khramova-Baranova, Olena; Khutka, Тetiana; Kudrevych, Viktoriia; Ishchenko, Yuri (European Science, 2025)
Fashion illustration is an artistic genre that specializes in fashion image, including clothing, accessories and images in general. Often used to visualize design ideas, create concepts for fashion collections, advertise and promote brands, as well as fo